Understanding HRM financial value from obtaining more star performers: introduction on a paper and commentary collection - Sanders, Karin; Fisher, Sandra L.; Dickmann, Michael (Taylor and Francis, 2023)
Joo, Aguinis, Lee, Kremer and Villamor demonstrated in their article entitled HRM’s financial value from obtaining more star performers in the International Journal of Human Resource Management (HRM) the financial value of acquiring star performers by using utility analysis on 206 samples of individual performance encompassing 824,924 workers. The analyses showed that HRM adds greater financial value by obtaining more star performers. Four (teams of) scholars, Michael Sturman, Xueging Fan, and Hanbo Shim, Michal Biron, Carol Kulik, and Mark Huselid responded to an invitation to comment on this article. In this introduction of the first commentary collection, we provide short summaries of the Joo et al. article and the four commentaries and discuss future research.
Keywords: Talent management; Star performers; HRM financial values; utility analysis